'Request Denied': Some Elements of a Sociology of Translation and Treason for Border and Migration Studies - Scheel, Stephan (Geopolitics, 2023)
Digital information and identification technologies offer state authorities new means for rendering individual subjects and entire population legible. Based on fieldwork at a migrant reception centre in Berlin, this article investigates how migrants hitherto unknown to authorities are translated into re-identifiable, governable subjects with the help of various digital devices. Conceptually, the article complements a sociology of translation with a vocabulary of treason to better account for coercion, force and violence as well as instances of resistance, friction and break-down in the assembling of related socio-technical networks. It shows that such an ANT-inspired framework, while facilitating a radically situated analysis, allows for exposing larger strategies of power. Through a detailed analysis of migrant registration procedures the paper develops three interrelated arguments on the digitisation of border and migration management: First, processes of digitisation are not reducible to the securitisation of migration. They are interrelated with the logistification of migration management which revolves around a logic of efficiency. The link between the digitisation and the logistification of migration management resides, secondly, in authorities' attempts to establish migrants' traceability. This is accomplished through the production of biometric identifiers and the allocation of personal identification numbers (PINs) which function as spokespersons for migrants. The fact that migrants often have to contest accounts shared by these informants in future encounters with authorities highlights, thirdly, that the production of legibility by digital means involves significant degrees of ontological violence.